Application of response surface methodology (RSM) to optimize COD and ammoniacal nitrogen removal from leachate using moringa and zeolite mixtures - Daud, Zawawi; Abubakar, Mahmoud Hijab; Rosli, Mohd Arif; Ridzuan, Mohd Baharudin; Awang, Halizah; Aliyu, Ruwaida (International Journal of Integrated Engineering, 2018)
This paper reported the optimization of COD and NH3-N reduction from a stabilised leachate by zeolite (ZE) and moringa oleifera leaf powder (MP) mixture using response surface methodology (RSM) and central composite design (CCD). Quadratic polynomial equations were obtained for the removal process. An initial experiment was conducted to establish the optimum mixed ratio between ZE:MP and resulted in a ratio of 24:16. Independent variables investigated in the subsequent optimization experiments include pH ,dosage and contact time. The results revealed that the optimal reduction of COD and NH3-N from landfill leachate was considerable at pH 5.9 , optimal time of 113 minutes and 100gL-1 of adsorbent dosage with desirability value of 0.917. The upper limits for the actual versus predicted reduction were 70.14 against 69.13%Â and 86.94 against 86.55 % respectively for COD and NH3-N which defined that the experimental values were relatively close to the predicted values. The study also revealed that ZE:MP mixture has a very high potential for the remediation of COD and NH3-N from a stabilized leachate.